" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
6b(2a-b)+2(3a+2b)(3a-2b)-18a²=
=12ab-6b²+2(9a²-4b²)-18a²=
=12ab-6b²+18a²-8b²-18a²=
=12ab-14b²=
12ab-6b kwadrat+(6a+4b) razy (3a-2b)-18a kwadrat
12ab-6b kwadrat +18a kwadrat - 12ab + 12ab - 8b kwadrat - 18a kwadrat
12ab - 12b kwadrat
w trzeciej linijce redukuje sie + 18a kwadrat z -18a kwadrat i -12ab z +12ab
12ba-6b"kwadrat"+2[(3a)"kwadrat"-(2b)"kwadrat"]-18a"kwadrat"=
12ab-6b"kwadrat"+2[9a"kwadrat"-4b"kwadrat"-18a"kwadrat"=
12ab-6b"kwadrat"+18a 'kwadrat"-8b"kwadrat"-18a"kwadrat"=
12ab-14b"kwadrat"